A case of hypokalemic myopathy induced by excessive drinking of a beverage containing green tea extract - Yamashiro, Nobuo; Nagasaka, Takamura; Fukumoto, Megumi; Kobayashi, Fumikazu; Takiyama, Yoshihisa (Rinsho Shinkeigaku, 2013)
A 49-year-old man subacutely developed muscle weakness in four extremities over a few days. He had no past or family history of muscle weakness. His blood tests showed significant hypokalemia without endocrinological abnormalities. With the diagnosis of hypokalemic myopathy, potassium was administered orally, and his symptoms improved. The patient had been drinking a beverage containing green tea extract too much two weeks before the symptoms developed, in addition to taking a cold remedy for ten years. Thus, hypokalemia is considered to be induced by the excessive intake of caffeine that accompanies the excessive consumption of the beverage and cold remedy.